ISLAMIC COMMERCIAL BANK BUSINESS STRATEGY DURING GLOBAL PANDEMIC OUTBREAK - Aditya Pratama; Warsiyah Warsiyah; Dwi Nastiti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
In 2020, the Covid-19 pandemic and how to handle it colored the development of the global economy. Millions of people have died and some are now out of work after being laid off. The pandemic has reduced world consumption, production, investment, and trade activities. The government and regulators side adjusting the benchmark interest rate and issuing relaxation and restructuring rules to prevent a bigger impact and encourage economic recovery. Using descriptive qualitative methods, this study tries to explore the business strategies implemented by five Islamic commercial banks with the largest assets, namely Bank Syariah Mandiri, Bank Rakyat Indonesia Syariah, Bank Nasional Indonesia Syariah, Bank Muamalat Indonesia, and Bank Aceh Syariah. all Islamic commercial banks optimize the digitization of services, both financing and fundraising. Focus on low-cost funds and conduct temporarily credit relaxation and restructuring for debtors who are experiencing financial difficulties due to the pandemic